Modeling and validation of an active chilled beam terminal unit - Ji, Ke (2021)
In this paper, a simplified hybrid model is proposed for an active chilled beam (ACB) terminal unit. Based on the conservation equations of mass and energy, the model demonstrates the air entrainment characteristics in the air chamber and the heat transfer process in cooling coil. Compared with the existing ACB model, the proposed model not only can capture the effects of the air buoyancy but also can reduce the complexity of the cooling coil model. This model requires only two equations with nine unknown coefficients that can be identified by the Levenberg-Marquardt method. Experimental validation in the thermal room proves that the proposed model is effective to predict the flow rate of supply air and heat transfer process in a wide range of operating conditions. Moreover, the proposed model can be further examined in optimization and performance evaluation applications for the ACB system.